2022
DOI: 10.2106/jbjs.22.00283
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Failures in Magnetic Intramedullary Lengthening Nails

Abstract: Background: Magnetic intramedullary lengthening nails (MILNs) have gained popularity in recent years for the treatment of limb-lengthening discrepancies. We sought to catalog mechanical failures and their prevention and management in a large, single-institution series. We specifically assessed the rate of mechanical failures, the types of failures observed, and management strategies.Methods: We retrospectively reviewed 377 patients (420 limbs) who underwent limb lengthening with early (P1) or later (P2) MILN i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Standard nail removal instruments may not be sufficient to extract broken PRECICE® nails. Hlukha et al reported an intra-operative disintegration of PRECICE® nail upon extraction which required collecting pieces with pituitary forceps [3] . In this case report, the motor unit elements disintegrated outside of the medullary canal and subsequently easily removed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Standard nail removal instruments may not be sufficient to extract broken PRECICE® nails. Hlukha et al reported an intra-operative disintegration of PRECICE® nail upon extraction which required collecting pieces with pituitary forceps [3] . In this case report, the motor unit elements disintegrated outside of the medullary canal and subsequently easily removed.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining length capacity can be determined based on knowledge of the consumed length. It is not recommended to reactivate nails which have reached their maximum length due to probability of distraction mechanism jamming [3] . Re-activation of lengthening nails for more than once should be extremely avoided.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first 2 generations of magnetic intramedullary lengthening nails used at a single institution, 40 (9.5%) of 420 failed and 63% of those required an additional surgical procedure. Many of these failures happened during the lengthening process, leading the authors to suggest close monitoring of nail distraction and weight-bearing 22 . In the second study, limb lengthening was performed with a novel motorized expandable plate for 7 children who were 2.7 to 9.7 years of age.…”
Section: Limb Deformity and Reconstructionmentioning
confidence: 99%